The Socio-Pedagogical Environment of Primary School Students in the Context of a Socially Distanced Classroom - Carpentier, Geneviève; Sauvageau, Claudine; Roy, Normand (Canadian Journal of Education / Revue canadienne de l'éducation, 2022)
In the context of the COVID-19 pandemic, classroom activities in the primary school, marked by physical distancing between students and teachers, raise some challenges. Thus, this article seeks to document the primary school students’ perceptions regarding their socio-pedagogical environment in the context of a socially distanced classroom. For this purpose, responses to the Questionnaire sur l’environnement sociopédagogique au primaire (QESPP) provided by 1,002 students aged from six to 12 in the fall of 2020 were subjected to descriptive quantitative analyses and to some comparative inferential analyses (SPSS 23.0). Results show a strong tendency of students’ positive perceptions toward the various climates of their socio-pedagogical environment, although the relational climate seems to be perceived somewhat less positively.